Multimodal text analysis - O'Halloran, Kay; Smith, B. (Wiley-Blackwell, 2013)
Multimodal text analysis has become a crucial part of research, teaching and practice for a wide range of academic and practical disciplines. A variety of techniques, theoretical frameworks, and methodologies have therefore evolved for such analysis. For linguists, in particular, concerned with accounting for the communication of meaning within texts, issues arising from the consideration of semiotic resources other than language, in interaction with each other and with language - such as gesture, gaze, proxemics, dress, visual and aural art, image-text relation and page layout, cinematographic and sound design, production resources, and so forth - have emerged in recent decades as important challenges. Meanwhile, the emergence of multimodal studies as a distinct area of study in linguistics has also revealed a range of issues specifically relevant tot he multimodal text analyst.